Analisis Faktor Dominan yang Berhubungan dengan Kejadian Gizi Kurang pada Balita di Kelurahan Pancoran Mas, Kota Depok. Jawa Barat - Nurmadinisia, Rahmi; Wulandari, Priharyanti; Susilawati, Susilawati (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
One of the unresolved health problems in Indonesia is undernutrition in toddlers which contributes to the low quality of human resources in Indonesia. Factors associated with the onset of undernutrition in toddlers include low birth weight (LBW), exclusive breastfeeding, basic immunization coverage in toddlers, and also have a close correlation with maternal characteristics in these toddlers such as maternal education, maternal employment, maternal nutritional status, gestational age and history of pre eclampsia during pregnancy. The study aims to see the dominant factors associated with the incidence of malnutrition in children under five so that appropriate intervention and prevention efforts can be determined so that there is no increase in cases of malnutrition. This study is an analytic obesrvational study with a cross-sectional approach and chi square test design. This research was conducted in September 2024. This research data comes from primary data, which includes, nutritional status of toddlers, mother's education, mother's work, mother's age during pregnancy and the addition of secondary data in the form of LBW history, history of pre eclampsia during pregnancy, and nutritional status of the mother during pregnancy. The population of this study was toddlers in Pancoran Mas village which amounted to 1,921 toddlers. The sampling technique used was cluster random sampling with a total sample of 97. Based on the results of research on the dominant factors associated with the nutritional status of toddlers, it was found that the dominant factor associated with the nutritional status of toddlers is the nutritional status of the mother.